2020
DOI: 10.3390/ijerph17072543
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nationality in Ultra-Endurance Sports: The Paradigm of Cross-Country Skiing and Long-Distance Running

Abstract: Although the variation of performance by nationality in endurance sports such as marathon has been well studied, little information exists so far on the role of nationality on performance in ultra-endurance sports. The aim of the present study was to review the role of nationality on cross-country skiing and ultra-endurance running. Scopus and PubMed were searched using the syntax “nationality AND (ultra-endurance OR ultra-marathon OR cross-country skiing) in 1/4/2020. This search identified 17 articles, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Ironman ® ‘70.3’ refers to the total distance in miles (113.0 km) of the race, consisting of a 1.2 mile swim, a 56 mile bike ride, and a 13.1 mile run. Among different research topics involving endurance athletes, the interest in understanding the environmental characteristics related to the place of competition and country of origin of the athletes has increased over the last few years [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ironman ® ‘70.3’ refers to the total distance in miles (113.0 km) of the race, consisting of a 1.2 mile swim, a 56 mile bike ride, and a 13.1 mile run. Among different research topics involving endurance athletes, the interest in understanding the environmental characteristics related to the place of competition and country of origin of the athletes has increased over the last few years [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the country of origin of long-distance triathletes, it has been reported that most finishers, as well as the fastest athletes competing in ‘Ironman ® Hawaii’, originated from the United States of America [ 7 ]. Although the previous literature has showed the dominance of certain nations in specific sports disciplines [ 4 , 6 , 8 , 9 ], little evidence is available regarding the place of competition or if these characteristics are performance-related. As the most popular long-distance triathlon in the world, athletes travel hundreds of miles to compete in Ironman ® 70.3 events, with many travelling thousands of miles to compete at remote locations and achieve personal goals or to earn a spot in the World Championship.…”
Section: Introductionmentioning
confidence: 99%
“…It is an interesting phenomenon that athletes originating from a specific region or country are dominating certain sports disciplines [ 1 ]. In running, for example, athletes originating from Jamaica have historically dominated in sprint events (100 m, 200 m and 400 m) [ 2 ], whereas athletes from East Africa (i.e., Ethiopia and Kenya) are some of the fastest runners over middle distance [ 3 ] and the marathon distance [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%